2020
DOI: 10.18764/1981-6421e2020.2
|View full text |Cite
|
Sign up to set email alerts
|

First Record of Bicephaly in the Brazilian Sharpnose Shark, Rhizoprionodon Lalandii

Abstract: Congenital deformities are relatively common in rays and sharks. The present study aimed to describe a case of bicephaly in an R. lalandii embryo. Through radiographic images and evaluation of the external and internal condition of the embryo in comparison with a young of the year with no deformities of the same species, it was possible to characterize the abnormality observed. Such data are important to determine the frequency and types of anomalies observed in elasmobranchs, thusallowing greater knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…However, the aetiology of cojoined twinning is still uncertain (Sans‐Coma et al., 2017). Over 24 shark specimens with this anomaly have been recorded worldwide (Ehemann et al., 2016; Kanagusuku et al., 2020; Lamarca et al., 2017; Prado et al., 2020; Sans‐Coma et al., 2017), with Prionace glauca being the most frequent species. In contrast, at least three batomorph cases with this anomaly are available, two for Rhinoptera spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the aetiology of cojoined twinning is still uncertain (Sans‐Coma et al., 2017). Over 24 shark specimens with this anomaly have been recorded worldwide (Ehemann et al., 2016; Kanagusuku et al., 2020; Lamarca et al., 2017; Prado et al., 2020; Sans‐Coma et al., 2017), with Prionace glauca being the most frequent species. In contrast, at least three batomorph cases with this anomaly are available, two for Rhinoptera spp.…”
Section: Discussionmentioning
confidence: 99%
“…Various teratological conditions have been reported in chondrichthyans, including bicephaly (Bornatowski & Abilhoa, 2009; Galván‐Magaña et al, 2011; Guida et al, 2013; Muñoz‐Osorio et al, 2013; Prado et al, 2020), cyclopia (Cabanillas‐Torpoco et al, 2023), anophthalmia (Ehemann et al, 2022; Rolim et al, 2020), albinism (Clark, 2002; Sandoval‐CaStillo et al, 2006), and assorted skeletal deformities (Bonfil, 1989; Moore, 2015; Wosnick et al, 2019; Zaera & Johnsen, 2011). Malfusion of the pectoral fins and head is one of the more commonly reported teratological conditions in the batoid elasmobranchs (Batoidea) (Ehemann et al, 2022), and the rostral malformation observed here is similar to occurrences in Rogers' round ray Urotrygon rogersi (Jordan & Starks 1895) (Mejía‐Falla et al, 2011) and Kuhl's maskray Neotrygon kuhlii (Müller & Henle 1841) (Ranjith et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…Within the last two decades, reports of abnormalities in elasmobranch embryos have increased worldwide, and a wide variety of abnormal morphological conditions have been described. The reports come from a range of seas and oceans, including the Atlantic Ocean (Clark, 2002; Coelho & Erzini, 2006; Mancini et al ., 2006; Delpiani et al ., 2011; Zaera & Johnsen, 2011; Wagner et al ., 2013; Dos Santos & Gadig, 2014; Afonso et al ., 2016; Lamarca et al ., 2017; Ramírez-Amaro et al ., 2019; Prado et al ., 2020), Pacific Ocean (Goto et al ., 1981; Clark, 2002; Bejarano-Álvarez et al ., 2011; Galván-Magaña et al ., 2011; Hevia-Hormazábal et al ., 2011; Bejarano-Álvarez & Galvãn-Magaña, 2013; Muñoz-Osorio, et al ., 2013; Escobar-Sanchez et al ., 2014; Becerril-García et al ., 2017; Pastén-Marambio et al ., 2018; Rodriguez-Romero et al ., 2019), Mediterranean Sea (Saidi et al ., 2006; Bottaro et al ., 2008; Sans-Coma et al ., 2016), Caribbean (Ehemann et al ., 2016) and Indian Ocean (Moore, 2015).…”
Section: Introductionmentioning
confidence: 99%